Fasies dan Lingkungan Pengendapan Karbonat di Gua Gadung, Desa Pundung Sari, Kecamatan Semin, Kabupaten Gunung Kidul, Daerah Istimewa Yogyakarta - Erlandi, Muhammad; Kurniawan, Sandi; Rizqi, Al Hussein Flowers; Nadip, Muhammad (ReTII, 2023)
Research area on Facies and Environment of Carbonate Rock Deposition of Wungkal-Gamping Formation located in Gadung Cave, Pundung Sari Village, Semin District, Gunung Kidul Regency, Special Region of Yogyakarta with geographical position 7o 53â€™32.2â€S and 110o 46'09.1â€E. Not many ordinary people or researchers know the location of Gadung Cave, let alone carry out in-depth studies, so a detailed study of the facies and depositional environment of the rocks in the research area needs to be carried out. The research area regionally belongs to the Wungkal Formation, which is found locally and is located between the Semilir and Mandalika Formations to the north of Mount Panggung, Semin Gunung Kidul. The purpose of this research is to identify the facies and depositional environment through field observation and petrographic analysis. The research method is from petrographic analysis of 3 sample petrographic thin section taken in Gadung Cave. The results of rock determination and description obtained facies in the form of Wackestone, Corraline Bindstone, and Foraminifera Rudstone. After identification and plotting to a depositional environment model in the standard limestone facies belt, it was found that this area was once a Reef Margin to the Toe-of Slope. Withdrawal of the age of the rocks in the limestone fragments in the bed breccias beneath the Gadung Cave. Relative age analysis to obtain the age of N3 (Late Oligocene) indicates that it is possible that the Gadung Cave carbonate rocks were deposited before the existence of the Semilir Formation. Keywords : Gadung Cave, Carbonate facies, Wungkal-Gamping, Semin